Penerapan Asas Aut Dedere Aut Punere Bagi Warga Negara Indonesia Pelaku Pembunuhan Di Arab Saudi Dikaitkan Dengan Konvensi Wina 1963 Tentang Hubungan Konsuler - Putra Zenno Januarsyah, Mas; Saepulloh, Aep (Cv. Kalimasada Group, 2025)
Law enforcement against Indonesian citizens (WNI) who commit serious crimes abroad, particularly murder in Saudi Arabia, poses challenges in implementing the principle of aut dedere aut punire and protection under the 1963 Vienna Convention on Consular Relations. This study aims to analyze the discrepancy between judicial practices in Saudi Arabia and the consular protection obligations of the sending state (Indonesia). Using normative juridical methods and a case-based approach, this study finds that Saudi Arabia prioritizes territorial jurisdiction and sharia law in prosecuting perpetrators, without considering extradition. Meanwhile, the implementation of consular protection is often suboptimal due to delays in information and diplomatic obstacles. This study recommends strengthening legal diplomacy and increasing bilateral cooperation for more effective protection of Indonesian citizens involved in serious legal cases abroad.